Can Transition to Adult Care for Transplant Recipients Be Improved by Intensified Services While Patients are Still in Pediatrics?. (September 2015) - Annunziato, Rachel A.; Parbhakar, Meera; Kapoor, Kathryn; Matloff, Robyn; Casey, Nicole; Benchimol, Corinne; Hotchkiss, Hilary; Nair, Vinay; Saland, Jeffrey
Context—: Transferring out of pediatrics is a vulnerable time for transplant recipients. Use of a transition coordinator before and after transfer improves outcomes, although it is unclear whether placing a transition coordinator in pediatrics alone is beneficial. Objective—: To determine if incorporating a transition coordinator in pediatrics only is associated with stable outcomes for kidney transplant recipients. Design—: A retrospective chart review was conducted on outcomes for kidney transplant recipients who shifted service location between 2008 and 2012. Setting—: A pediatric and adult transplant unit. Patients—: Twenty-two patients transferred during the study period. Intervention—: Twelve patients received more intensified preparation from the team's social worker, whose role was aligned with a transition coordinator position; 10 patients received standard care. Main Outcome Measures—: The primary outcome was medication adherence, using a validated measure, standard deviations of tacrolimus blood levels. A standard deviation greater than 2.5 has been established as a threshold associated with poor outcomes such as rejection. Standard deviation of tacrolimus levels was compared for 1 year before and 1 year after transfer. Results—: Medication adherence worsened from 1 year before (2.03 [SD, 0.75]) to 1 year after transfer (2.95 [SD, 1.38]; t = −3.07, P = .007). A repeated-measures analysis of variance indicated that this pattern was the same for patients who did and patients who did not receive intensified services in pediatrics ( F 1, 16 = 1.07, P = .32).